MR neurography: normative values in correlation to demographic determinants in children and adolescents - Hofstadler, Barbara; Bäumer, Philipp; Schwarz, Daniel; Kronlage, Moritz; Heiland, Sabine; Bendszus, Martin; Godel, Tim (Clinical neuroradiology, 2019)
To determine normative morphological and functional magnetic resonance (MR) neurography values in children and adolescents in correlation to demographic determinants.